32‐1: Weak Sub‐color Sub‐sampling for High Resolution Image Bandwidth Reduction. Issue 1 (25th September 2020) - Lee, Joonhee; Park, Dongwon; Kim, Changgone; Yoon, Sooyoung
Abstract : This paper provides a novel image processing and interface technique that can reduce its data bandwidth simply without critical image quality degradation so that a real‐time high resolution display system can save its power and cost. It analyzes each sub‐color with respect to its contribution to an original image to decide which sub‐color is the least‐contributed ('Weak sub‐color data') and how to reduce its transmission bandwidth. The input image or video data can be converted into a combination of some of original sub‐color data and some of 1: N sub‐sampled sub‐color data having the smallest contribution. If N = 4 for one sub‐color, the data transmission rate is reduced by 25%, and if N > 4 for one sub‐color, the required data bandwidth for transmission can be reduced further. This enables more efficient and low cost implementations in various high resolution display systems.